Effectiveness of Archives Management Reviewed from Management Factors in Pattallassang Sub-District Office in Gowa regency - Henni Zainal; Andi Idham Ashar; Andi Tenry Sose; Darmawati Manda; Ignasius Setitit (Universitas Negeri Makassar, 2020)
Archives has a role as a center of memory, resources and as a necessary means of supervision in every organization in order to carry out all its activities both in the offices of state and private institutions.The purpose of this research is to find out the management of archives reviewed from management factors in the District Office Pattallassang Gowa Regency.The research method used is qualitative by survey method, namely research that intends to obtain facts from the phenomena in order to understand and solve problems related to factors that affect the effectiveness of archive management in the District Office Pattallassang Gowa Regency. Data collection techniques used are observations, documentations and interviews. Conclusion in this research is a management factor, it is expected to do the purging of archives above 5 years with clear recording and supervision and evaluation of activities after the activity in order to know the advantages and disadvantages of the activity so that the next activities can be maximized better.